The Effectiveness of Flashcards and Dragon Games in Teaching English Vocabulary to Kindergarten Students - Khoiriyah, Nurul; Hawa, Faiza; Setyaji, Arso (LPPM Universitas Pekalongan, 2025)
Introducing vocabulary to kindergarten children is difficult, especially for foreign languages. They need clear visuals to illustrate a word. Based on the researcher's experience at BiMBA Kindergarten, students were less interested and less motivated in learning English because the learning methods and media were less interesting. Therefore, the researcher aims to conduct this study to assess the effectiveness of the methods and media used on vocabulary mastery. This research was conducted at BiMBA Genuksari with a sample of 30 kindergarten students. A quantitative research method was applied using a pre-experimental design with a pre-test, post-test, and observation as data collection. The results showed the statistical analysis using a paired sample t-test produced a p-value of 0.000, indicating a significant difference after treatment. The observation results also showed that students' learning motivation increased after treatment. Therefore, teachers can use flashcards and dragon games to create an engaging and student-centered learning environment. Keywords : Dragon Game, Flashcard, Vocabulary